2022
DOI: 10.3390/gels8120802
|View full text |Cite
|
Sign up to set email alerts
|

Preparation Method and Performance Evaluation of a Gel Based on AM/AMPS Copolymer

Abstract: Polymer gels have been widely used in high water cut oilfields for profile control and water plugging. It is urgent to develop a gel suitable for the Tahe Oilfield (Temperature: 130 °C, salinity: 2.2 × 105 mg/L) in China. A stable gel was prepared by using an acrylamide (AM)/2-acrylamide-2-methyl propanesulfonic acid (AMPS) copolymer crosslinked with urotropin (HMTA), hydroquinone (HQ), thiourea and Nano-SiO2. This paper covers a step-by-step process for designing gels based on experience with preparing gels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…In addition, the storage modulus of the gel was evaluated using a rheometer at a temperature of 25 °C. The setting method of the instrument can be referred to our previous article [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the storage modulus of the gel was evaluated using a rheometer at a temperature of 25 °C. The setting method of the instrument can be referred to our previous article [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…After sealing the sample, the gelation time and gel strength were observed at ambient temperature. In addition, the storage modulus of the gel was evaluated using a rheometer at a temperature of 25 • C. The setting method of the instrument can be referred to our previous article [34].…”
Section: Determination Of Gelation Time and Strength Of Gelmentioning
confidence: 99%
“…We list a variety of temperature-resistant copolymer gels, as shown in Table , and it can be seen that the most commonly used temperature-resistant monomer is AMPS. Using cyclic hexamethylenetetramine and phenolic compounds to cross-link AM/AMPS copolymers, the gels can be made to persist at 130 °C for 30–100 days, the main mechanism being the cross-linking of the amide group of the copolymers (−CONH 2 ) with the hydroxyl group of the phenolic compounds (−CH 2 OH). It has been suggested that the AMPS/AM copolymer system has better thermal stability mainly due to the following reasons. , (1) AMPS has a long branched chain and sulfonic acid groups, which make AMPS more thermally stable than AM.…”
Section: Improved Gel Performancementioning
confidence: 99%
“…Polymer ooding is an important tool for oil eld development to further improve recovery, but it faces challenges in high saline reservoirs. 9,10 polymer ooding an enhanced oil recovery method that utilises high molecular weight polymers to increase the viscosity of injected uids, thus improving sweep e ciency and altered mobility ratio between oil and injected uid. 11,12 Although the effect is not ideal for the non-heterogeneity characteristics of highly mineralised reservoirs.…”
Section: Introductionmentioning
confidence: 99%